Can kidneys be saved in patients with urinary tuberculosis? A study in the era of modern chemotherapy and surgical armamentarium. (25th February 2019) - Kumar, Amar; Dangi, Anuj D; Mukha, Rajiv P; Panda, Arabind; Jeychandraberry, Chandrasingh; Kumar, Santosh; Devasia, Antony; Kekre, Nitin S
Abstract : Objective: To assess renal unit survival and factors affecting renal salvageability in a cohort of patients receiving modern medical and surgical therapy for urinary tuberculosis. Methods: This was a retrospective single‐center study including all patients diagnosed and treated as urinary tuberculosis between 2005 and 2015 at Christian Medical College, Vellore, Tamil Nadu, India. The primary outcome was time to renal unit non‐salvageability (estimated glomerular filtration rate of <15 mL/min). Results: A total of 128 patients were included in the study. The mean age was 37.7 ± 11.3 years, 33% had microbiological and 73% had histopathological confirmation in addition to radiological diagnosis. The estimated median survival of the involved renal units ( n = 187) on Kaplan–Meier estimate was 75 months (95% CI 39–99). On multivariate analysis, renal units with initial split function >15 mL/min had fivefold the survival estimate as compared with those ≤15 mL/min ( P < 0.001); the presence of one, two and three infundibular strictures had a 2.2‐, 2.9‐ and fivefold higher hazard of renal unit loss respectively, and lower ureteric strictures had fivefold longer estimated survival ( P = 0.015) after treatment. Renal units in the reconstruction group had 5.44‐fold (95% CI 2.71–10.88, P < 0.001) longer survival than the permanent diversion group, with a mean change in split function of +0.76 (±16.11) mL/min, versus −5.61 (±10.87) mL/min respectively. Conclusions: Loss of renal units is a function of time despite modern treatment. Baseline renal unit function, site of ureteric involvement and extent of infundibular involvement on imaging are helpful in predicting the duration of renal salvageability. When feasible, reconstruction is better at renal function preservation.